Natural pasture evaluation under different intensities of grazing with clover introduction, mowing and burning. - Gonzaga, Sérgio Silveira; Jaques, Aino Victor Ávila (Pesquisa Agropecuaria Brasileira, 2014)
The effects of sod-seeding Yuchi arrowleaf dover (Trifolium vesiculosum Savi), mowing or burning on yield and quality of a natural pasture submitted to two grazing intensities by sheep, were studied. The experiment was carried out at EEA/UFRGS, in Guaíba, RS, Brazil. A split-plot design in randomized blocks was used. The samples were collected every eight weeks. The introduction of Yuchi dover on the natural pasture has significantly boosted the DM yield and the percentage of CP. The average available DM over six harvests was respectively 2677, 1279 and 1175 kg/ha for dover introduction, mowing and burning. The intensive grazing by sheep on the natural pasture has significantly increased the CP percentage and DOM